Empyema Secondary to Actinomyces meyeri Treated Successfully with Ceftriaxone Followed by Doxycycline - Paris, Etienne (Case Rep Infect Dis, 2016)
Actinomycosis is a relatively rare infection caused by Gram-positive bacteria. We present the case of a 54-year-old, previously healthy, male patient with a history of severe penicillin allergy who developed severe pneumonia and empyema caused by Actinomyces meyeri. Presenting symptoms included productive cough, right upper quadrant pain, and chills and rigors. He required drainage of the empyema via tube and prolonged antibiotic treatment with intravenous ceftriaxone for 2 weeks followed by oral doxycycline for 6 months.